Cover Image, Volume 31, Issue 1. Issue 1 (19th December 2021) - Adamson, Blythe J. S.; Ma, Xinran; Griffith, Sandra D.; Sweeney, Elizabeth M.; Sarkar, Somnath; Bourla, Ariel B.
Abstract : The cover image is based on the Original Article Differential frequency in imaging‐based outcome measurement: Bias in real‐world oncology comparative‐effectiveness studies by Blythe J. S. Adamson et al., https://doi.org/10.1002/pds.5323 .